Organization of circadian rhythms of sex hormone secretion in female students with vegetative-vascular dystonia of the hypertensive type involved in fitball gymnastics - Milashechkina E.A. ,; Rusanova E.I. ,; Dzhandarova T.I. ,; Gernet M.S. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to determine the effect of a course of additional fitball aerobics classes on the circadian rhythms of sex hormones in female students with vegetative-vascular dystonia of the hypertensive type. Methods and structure of the study. The scientific work was carried out on the basis of the North Caucasus Federal University. Sex hormones in saliva were analyzed using a highly sensitive competitive immunological method. Collections were made at 8.00, 12.00, 16.00, and 20.00 at the beginning of the school year and at the end. Cosinor analysis was carried out using a computer and the Cosinor Ellips 2006 program installed on it. The study involved female students with hypertensive VSD (n=58), female students with hypertensive vegetative-vascular dystonia, and female students with hypertensive vegetative-vascular dystonia who practice fitball. -gymnastics (n=50), and practically healthy female students of the main group (n=50). Results and conclusions. In female students with vegetative-vascular dystonia of the hypertensive type, engaged in fitball gymnastics, positive changes were revealed in stabilizing the circadian rhythm of estradiol concentration, rhythmostasis of testosterone concentration was still not detected.